"Greening" and comfort conditions in transport infrastructure systems: Understanding users' preferences. (15th May 2021) - Benoliel, Maria Ana; Manso, Maria; Ferreira, Patrícia Dinis; Silva, Cristina Matos; Cruz, Carlos Oliveira
Abstract: Urban planners, policy makers and transport operators constantly search for ways to improve the environment of transport infrastructures. "Greening" solutions, such as green roofs and walls, are among the potential measures to achieve the Sustainable Development Goals. The integration of greenery in the urban environment, including transport infrastructures, is shown to provide positive Net Present Values and to have several environmental, economic, and social benefits. Since users are forced to walk and wait in urban interfaces for a certain time, "greening" solutions may contribute to improve their psychological well-being and comfort. However, there is little evidence on the perceptions and the value attributed by users to these solutions. This paper intends to provide a unique perspective on users' perception and willingness-to-pay for comfort and "greening" solutions in transport interfaces. The proposed methodology aims to evaluate the feasibility of several scenarios, based on a questionnaire survey taken amongst railway users. The process starts with a pilot survey and preliminary interviews, followed by the definition of the target population and with both "in-situ" and online survey campaigns. The case-study is developed at Entrecampos Station, Lisbon, Portugal, where the survey was taken by 146 users. Results have shown that although users might attribute some value to having greener spaces in public transport interfaces, their willingness-to-pay is low and they show a preference for improvements such as more seats or safe and comfortable waiting areas. These conclusions may assist decision-making processes regarding infrastructure systems and urban greening. Highlights: Identifying users' perception of comfort conditions at transport infrastructures. Analysis of users' preferences and willingness-to-pay for greening scenarios. Having an indoor garden is the most beneficial option to improve the users' comfort. Greener spaces are valued by users but their willing to pay (WTP) is low. Key investment is in integrated redesign merged with greening solutions.